AIAA AVIATION 2022 Forum 2022
DOI: 10.2514/6.2022-3856
|View full text |Cite
|
Sign up to set email alerts
|

Gas Injection into Second Mode Instability on a 7 degree Cone at Mach 7

Abstract: The influence of injection gas type on second mode instabilities is researched on a 7 • half-angle cone at Mach 7. The wind tunnel model of 594.5 mm length with a sharp nosetip is fitted with a porous aluminium patch that spans 60 • in azimuth and 25 mm in axial length. Four different gases are injected into the boundary layer flow, namely nitrogen, carbon dioxide, helium and argon. Three different tunnel test conditions with different Re u provide a variety of amplification levels of the second mode instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Transition onset for the transpiration cooling of cylindrically or spherically blunted bodies is an area of active research. Recent preliminary studies have showed that that mass injection on an axisymmetric nosetip may delay transition with moderate mass fluxes and light gases [34].…”
Section: Laminar Solvermentioning
confidence: 99%
See 1 more Smart Citation
“…Transition onset for the transpiration cooling of cylindrically or spherically blunted bodies is an area of active research. Recent preliminary studies have showed that that mass injection on an axisymmetric nosetip may delay transition with moderate mass fluxes and light gases [34].…”
Section: Laminar Solvermentioning
confidence: 99%
“…The only recent work on leading edges with distributed outflow have used slots [32], variable permeability [33], or multiple plenums and injectors [34,35]. These studies did not consider leading edge-only injection, and only [34] was carried out in a hypersonic facility, and took heat flux augmentation measurements. The rest were carried out in heated subsonic facilities, or in plasma facilities [36], taking temperature measurements only.…”
Section: Introductionmentioning
confidence: 99%
“…1, has been previously employed in the same configuration and injector by Kerth. 41,42 The model has a straight, sharp nose tip with a nose radius smaller than 0:05 mm as given by the manufacturer and is instrumented with high frequency differential pressure sensors (PCB132A31 and PCB132B38) and in-house manufactured thin film gauges (TFG). 43,44 To achieve a smooth surface finish, outer radii of the model were machined with a 0.02 mm tolerance, and individual segments of the model were lathed into the outer conical shape after they were assembled.…”
Section: Experimental Setup a Test Model With Gas Injectionmentioning
confidence: 99%
“…Their method to infer transition onset is based on comparing theoretically obtained laminar heat flux levels to averaged thermocouple data. 14 Work by Kerth et al 34 has dealt with a similar gas injection scenario, wherein transition was inferred from schlieren images and thin film gauges. Hereby, transition took place far away from the injection location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation